Itinérances politiques et éducatives franco-espagnoles. « Voir ce qui doit être vu » : les trois voyages d'Henri Wallon en Espagne républicaine de 1936 à 1938 - Mari Carmen Rodriguez (Recherches en Éducation)
From 1936 to 1938, Henri Wallon, a child psychologist, teacher at the Sorbonne, then at the Collège de France, went three times to the Spanish Republic at war. For the members of his generation who experienced it, the «war travel» to Spain is a multiple training tool and a vector of transnational circulations. The republican zone from 1936 to 1939 is a destination where anti-fascist militants converge, aware of the international scope of the conflict, as well as those who promote educational reforms. Actually, this territory constitutes a laboratory of «new education», inherited from a long period of exchanges between liberal elites since the 18th century, for whom education is a founding and emancipatory sharing. This contribution attempts to question these exchanges in the light of Wallon's political and educational itinerancy during his three stays, between Marxist commitment and anti fascism, humanitarian action and observation of the heritage of «new education» in Spain before its disappearance.